THE ROLE OF LOCAL GOVERNMENTS IN DELIVERING PUBLIC SERVICES IN PAKISTAN - Fazli Rahman; Dr. Yunas Khan‡; Shehla Javed (Journal of Religion and Society, 2024)
Local governments in Pakistan play a critical role in delivering public services, yet they face significant challenges that hinder their effectiveness. This study examines the historical, legal, and operational frameworks of local governance in Pakistan, focusing on the decentralization of power and the devolution of responsibilities to local bodies. Despite constitutional provisions and various reforms, local governments struggle with financial constraints, political interference, and inadequate capacity building, which limit their ability to provide essential services such as education, healthcare, and infrastructure. The paper highlights the disparities between urban and rural service delivery, emphasizing the need for greater financial autonomy, enhanced training programs, and reduced political influence to improve governance at the grassroots level. Case studies from provinces like Khyber Pakhtunkhwa and Punjab illustrate both successes and ongoing challenges in local governance. The study concludes with recommendations for strengthening local governments, including increasing revenue generation, fostering public-private partnerships, and leveraging technology to enhance service delivery. By addressing these issues, Pakistan can achieve more equitable and efficient public service provision, ultimately contributing to socio-economic development and improved quality of life for its citizens. Keywords: Local governments, Pakistan, public service delivery, decentralization, financial constraints, political interference, capacity building, urban-rural disparities, governance reforms, technology in governance